The Many Bodies of the First Statute of Lithuania - Čižauskas, Karolis (Vilnius University Open Series, 2024)
The category of the body is the main object of this study. The paper hopes to further examine the “corporal” theme in the research of the history of the Grand Duchy of Lithuania while simultaneously aiming to outline the countours of the concept. Being a legal codex, The First Statute of Lithuania (1529) was chosen as a foundational text for this study since it pertains to various aspects of both public and private life. Albeit not exhausting all possible interpretations, three bodies were examined more closely: that of a nobleman, of the grand duke, and of the state (the Grand Duchy) – each more abstract than the former. First of these can be associated with terms of status and honour, the second functions as if by extensions of ducal officers and medias, while the third is characterized by the matters of indivisibility, inalienation and membership. Moreover, three different properties (or faculties) were attributed to the body: epistemological (via senses and body marking), agential (as a mean to excercise one’s will and freedoms), and individualizing (as in the problem of belonging).
Keywords: body; the First Statute of Lithuania; monarch; nobility; political theology; law; Grand Duchy of Lithuania